Pengaruh E-trust dan E-satisfaction terhadap Continuance Intention Pengguna GoPay - Afri Septianingrini; Assyifa Mulandar; Abdul Yusuf (Jurnal Ilmiah Wahana Pendidikan, 2023)
The lifestyle of all levels of society required to live fast and instantaneously is accompanied by a digitalization process with a massive abundance of various sources and knowledge such as filling the wide gap between problems and solutions in this era of globalization. The availability of multiple shopping platforms and ease of transactions have made consumers flock to take advantage of online payment features. The emergence of the Covid-19 pandemic has also triggered changes in several fields, especially in the economic sector. Judging from the current conditions, people are certainly utilizing digital platforms with all the conveniences, benefits, and advantages, indicating that electronic money is very well received, especially by dense urban communities to prevent the spread of the Covid-19 virus. Therefore, the increasingly competitive competition in the digital wallet business must be able to create and maintain good quality electronic services. So it can increase trust for users of the application. The sample of this research is 100 respondents who have currently using GoPay. This primary data was collected by questionnaire. Data analysis with linear regression. The results showed that E-Trust and E=Satisfaction had a significant effect on the Continuance Intention of GoPay users.